Immunomodulatory Activities of Periodontal Ligament Stem Cells in Orthodontic Forces-Induced Inflammatory Processes: Current Views and Future Perspectives - Behm, Christian; Zhao, Zhongqi; Andrukhov, Oleh (Frontiers in Oral Health, 2022)
Orthodontic tooth movement (OTM) is induced by applying active mechanical forces, causing a local non-infectious inflammatory response in the periodontal ligament (PDL). As a prerequisite for OTM, the inflammation status is associated with increased levels of various cytokines and involves the interaction between immune cells and periodontal ligament stem cells (hPDLSCs). It is well established that hPDLSCs respond to orthodontic forces in several ways, such as by secreting multiple inflammatory factors. Another essential feature of hPDLSCs is their immunomodulatory activities, which are executed through cytokine (e.g., TNF-α and IL-1β)-induced production of various soluble immunomediators (e.g., indoleamine-2,3-dioxygenase-1, tumor necrosis factor-inducible gene 6 protein, prostaglandin E2) and direct cell-to-cell contact (e.g., programmed cell death ligand 1, programmed cell death ligand 2). It is well known that these immunomodulatory abilities are essential for local periodontal tissue homeostasis and regeneration. So far, only a handful of studies provides first hints that hPDLSCs change immunological processes during OTM via their immunomodulatory activities. These studies demonstrate the pro-inflammatory aspect of immunomodulation by hPDLSCs. However, no studies exist which investigate cytokine and cell-to-cell contact mediated immunomodulatory activities of hPDLSCs. In this perspective article, we will discuss the potential role of the immunomodulatory potential of hPDLSCs in establishing and resolving the OTM-associated non-infectious inflammation and hence its potential impact on periodontal tissue homeostasis during OTM.